The effects of using recycled concrete on fatigue behavior of hot mix asphalt - Nejad, Fereidoon Moghadas; Azarhoosh, Ali Reza; Hamedi, Gholam Hossein (Journal of Civil Engineering and Management, 2014)
Fatigue cracking is the main form of structural damage in flexible pavements. Under the action of repeated vehicular loading, deterioration of the asphalt concrete materials in pavements caused by the accumulation and growth of the micro and macro cracks gradually takes place. The results of a laboratory study evaluating the fatigue properties of hot-mix asphalt (HMA) mixtures using indirect tensile fatigue test (ITFT) were investigated in this paper. The HMA mixtures containing 0%, 35%, 70%, and 100% of recycling concrete aggregate (RCA) were plant prepared with one source of aggregate, limestone, and one type of binder, 60/70-penetration grade. In this paper, it is shown that the use of recycled concrete produced by crushing demolished concrete elements can increase the efficiency of asphalt mixes, reduce primary production costs and prevent much fullness of the recycled materials in the environment. It was found that replacing up to 100% of the virgin aggregate by RCA improved the fatigue properties of the asphalt mixtures.